THE ROLE OF EDUCATION OF PEDAGOGICAL RESILIENCE IN STUDENTS – FUTURE TEACHERS - Shavilova Natalya Sergeyevna (American Journals, 2024)
The article describes trends in the development of education in the Republic of Uzbekistan, prospects and opportunities for the scientific and intellectual potential of the younger generation, and the introduction of modern technologies into the educational process. The key concept of the article is educational resilience – as a tool for the effectiveness of modern cognitive approaches in increasing educational performance.
Keywords: education system, harmoniously developed youth, modernization, professional activity, pedagogical resilience, cognitive approaches.